3 D Co3(PO4)2–Reduced Graphene Oxide Flowers for Photocatalytic Water Splitting: A Type II Staggered Heterojunction System. Issue 22 (15th November 2016) - Samal, Alaka; Swain, Smrutirekha; Satpati, Biswarup; Das, Dipti Prakasini; Mishra, Barada Kanta
Abstract: The design, synthesis, and photoelectrochemical characterization of Co3 (PO4 )2, a hydrogen evolving catalyst modified with reduced graphene oxide (RGO), is reported. The 3 D flowerlike Co3 (PO4 )2 heterojunction system, consisting of 3 D flowerlike Co3 (PO4 )2 and RGO sheets, was synthesized by a one‐pot in situ photoassisted method under visible‐light irradiation, which was achieved without the addition of surfactant or a structure‐directing reagent. For the first time, Co3 (PO4 )2 is demonstrated to act as a hydrogen evolving catalyst rather than being used as an oxygen evolving photoanode. In particular, 3 D flowerlike Co3 (PO4 )2 anchored to RGO nanosheets is shown to possess dramatically improved photocatalytic activity. This enhanced photoactivity is mainly due to the staggered type II heterojunction system, in which photoinduced electrons from 3 D flowerlike Co3 (PO4 )2 transfer to the RGO sheets and result in decreased charge recombination, as evidenced by photoluminescence spectroscopy. The band gap of Co3 (PO4 )2 was calculated to be 2.35 eV by the Kubelka–Munk method. Again, the Co3 (PO4 )2 semiconductor displays n‐type behavior, as observed from Mott–Schottky measurements. These RGO–Co3 (PO4 )2 conjugates are active in the visible range of solar light for water splitting and textile dye degradation, and can be used towards the development of greener and cheaper photocatalysts by exploiting solar light. Abstract : Catalyst in bloom : A type‐II heterojunction photocatalyst based on 3 D flowerlike Co3 (PO4 )2 on reduced graphene oxide (RGO) nanosheets is synthesized through a photoreduction route. The heterojunction has the unique property of generating hydrogen through photosplitting of water, unlikely the activity of pristine Co3 (PO4 )2 .